Association of Spontaneous Preterm Delivery and Future Maternal Cardiovascular Disease. Issue 8 (20th February 2018) - Minissian, Margo B.; Kilpatrick, Sarah; Eastwood, Jo-Ann; Robbins, Wendie A.; Accortt, Eynav E.; Wei, Janet; Shufelt, Chrisandra L.; Doering, Lynn V.; Merz, C. Noel Bairey
Abstract : Cardiovascular disease (CVD) risk factors are well established. However, little is known about a woman's cardiovascular response to pregnancy, which appears to be an early marker of future maternal CVD risk. Spontaneous preterm delivery (sPTD) has been associated with a ⩽3-fold increased risk of maternal CVD death later in life compared with having a term delivery. This review focuses on 3 key areas to critically assess the association of sPTD and future maternal CVD risk: (1) CVD risk factors, (2) inflammatory biomarkers of interest, and (3) specific forms of vascular dysfunction, such as endothelial function and arterial stiffness, and mechanisms by which each may be linked to sPTD. The association of sPTD with subsequent future maternal CVD risk suggests that a woman's abnormal response to pregnancy may serve as her first physiological stress test. These findings suggest that future research is needed to understand why women with sPTD may be at risk for CVD to implement effective interventions earlier in a woman's life.